Nānā Phadaṇavīsāñcẽ caritra - Khare, Vāsudeva Vāmanaśāstrī, 1858-1924 (SAMP early 20th-century Indian books project, 1927)
On the life and work of Nana Phadnis, 1742-1800, counselor of Peshwas of Maharashtra, India.